Characterization of enzymatic glucose biosensor in buffer solution, in artificial saliva, and in potassium ferricyanide by linear sweep voltammetry - Ramli, Nurul Izzati; Abd-Wahab, Firdaus; Wan Salim, Wan Wardatul Amani (AIP, 2018)
Existing practice of glucose-level monitoring for diabetic patients involves frequent finger pricking for blood samples. This is not only constantly painful, but could make patients susceptible to infections. A non-invasive, portable, graphene-based biosensor is being developed to measure glucose levels in saliva instead of in blood, by incorporating rGO-PEDOT:PSS composites as the transducer layer on a working electrode – a screen-printed carbon electrode (SPCE) 2 mm in diameter. To evaluate the performance of the biosensor, the electrochemical technique of linear sweep voltammetry (LSV) was used. The results showed sensitivity of rGO-PEDOT:PSS-GOx/SPCE in artificial saliva: 105 μA/mM (σ = 12.52) at no glucose to 0.2 mM glucose concentrations and 35.33 μA/mM (σ = 5.79) at glucose concentrations of 0.2 mM to 0.6 mM, with correlation coefficient of 0.99. The sensitivity of the biosensor in 10 mM PBS (pH 6.8) is 9.88 μA/mM (σ = 2.74), while in 100 mM potassium ferricyanide it is 10.48 μA/mM (σ = 0.49). The high sensitivity obtained in artificial saliva suggests that the rGO-PEDOT:PSS composite is suitable for use as a transducer layer for non-invasive glucose monitoring.